Cover Picture: Achievements of the Late Professor Teruaki Mukaiyama (Chem. Rec. 1/2021). Issue 1 (21st January 2021) - Murakami, Masahiro
Abstract : The Cover picture is a photo of the late Professor Teruaki Mukaiyama and his wife, Hiroko, taken whilst he was a graduate student at Tokyo Institute of Technology. Professor Mukaiyama was the founding editor of The Chemical Record and the Essay on his life by Masahiro Murakami (DOI: 10.1002/tcr.202000105 ) coincides with the 20 th anniversary of the Journal.